(untitled) (Fiep Bulletin - online, 2014)
So the objective of study present was identifying the somatotype profile of professional player’s football ground Brazilian selection Sub-20 accord with function tactics. The sample was of 21 athletes participants of world championship 2006; obtain the third collocation in the competition. Was sad weight corporeal, stature, perimeters, bone diameters and flexure cuteness’ accord with the protocol of Heath-Carter (1990) .The facts was presented by statistic descriptive with middle values diversion model general of 3,257±0,656 to endomorphic, 3,966±0,631 to mesomorphic and 2,214±0,658 to ectomorphic, respective minimum values of 2,0 - 2,5 - 1,1 and maximum of 4,8 - 4,9 - 3,6 and the interval of trust to the middle, to 95% of certainty. Accord with arrangement tactics had middle and diversion standard to endomorphic, mesomorphic and ectomorfphic of 3,5 ± 0,36 - 4,36 ± 0,68 e 1,9 ± 0,50 to goalkeepers (n=3); 3,6 ± 0,53 - 4,02 ± 0,55 - 2,25 ± 0,63 to fullback (n=4); 2,62 ± 0,48 - 3,62 ± 0,90 - 2,52 ± 0,97 to sideline (n=5) ; 3,65 ± 1,62 - 3,85 ± 0,77 - 2,05 ± 0,91 to steering (n=2) ; 3,5 ± 0,05 - 4,25 ± 0,43 - 2,0 ± 0,61 to middle (n=4) , 3,23 ±0,66 - 3,76 ± 0,25 - 2,36 ± 0,20 to attacker (n=3). It was verified that athletes of the Brazilian selection of Soccer of Field regarding the classification of the somatotype presented, predominance of characteristic meso-endomorphic, that is to say, where the muscle-skeletal magnitude is put upon to the corporal adiposity and the crossing of the tactical functions doesn’t depend on the classification somatotipic.